Expression levels of mRNA for neurosteroidogenic enzymes 17β-HSD, 5α-reductase, 3α-HSD and cytochrome P450 aromatase in the fetal wild type and SF-1 knockout mouse brain. (February 2015) - Spanic, Tanja; Fabjan, Teja; Majdic, Gregor
Abstract The presence of steroidogenic enzymes in the brain suggests de novo synthesis of steroid hormones in the brain. The current study was designed to determine the developmental profiles of cytochrome p450 aromatase (cyp19), 17β-hydroxysteroid dehydrogenase (17β-HSD), 5α-reductase type I and 3α-hydroxysteroid dehydrogenase (3α-HSD) mRNA expression levels in the fetal mouse brain and potential influence of peripheral steroids, and the steroidogenic factor 1 (SF-1) gene on their expression. Brains were collected from WT and SF-1 knockout male and female fetuses at embryonic (E) days E12, E14, E16, and E18. Quantitative PCR analyses revealed age related increases in the expression levels of 17β-HSD and 5α-reductase. Differences between genotypes in the expression levels of 17β-HSD and 5α-reductase were detected on E14, with reduced levels of expression in SF-1 KO males and females for 17β-HSD and only between females for 5α-reductase. Expression of 3α-HSD mRNA did not differ significantly between sexes, age groups or genotypes with the exception of SF-1 KO males, which had an unexplained increase in mRNA for this enzyme on day E18. Expression of cyp19 was at the limit of detection and could not be analyzed effectively. There were no sex differences and, with the exception of small difference on E14 for 17β-HSD and 5α-reductase, no differences between genotypes. The results suggest that gonadal steroids do not influence the production of neurosteroids in the fetal brain, nor does SF-1 play a major role in the regulation of steroidogenic enzyme expression in the brain.